2016
DOI: 10.3329/bjp.v11i4.27131
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive and diuretic activities of aqueous-ethanol extract of <i>Asphodelus tenuifolius</i>

Abstract: <p class="Abstract">In order to rationalize the traditional uses of <em>Asphodelus </em>tenuifolius in cardiovascular complaints, aqueous-ethanol extract of the plant was investigated for hypotensive and diuretic activities using <em>in vivo</em> and in vitro models. Intravenous administration of the extract in anesthetized rats produced 14.5 (95% CI; 13.3–15.6), 24.5 (95% CI; 21.3-27.9) and 35.3% (95% CI; 32.0–42.5)  fall in mean arterial blood pressure at the doses of 3, 10 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…The high concentration of potassium High-K + (K-80mM) in the extracellular fluid may result in the opening of voltageoperated calcium channels and leads to the contraction of smooth muscles. The compounds which cause the relaxation of K-80mM induced contractions in smooth muscles are considered as calcium channel antagonists [24][25][26]. The results of the present study have shown that the spasmolytic activity of thiophene derivatives may be due to the blockage of calcium channels.…”
Section: Spasmolytic Activitymentioning
confidence: 63%
“…The high concentration of potassium High-K + (K-80mM) in the extracellular fluid may result in the opening of voltageoperated calcium channels and leads to the contraction of smooth muscles. The compounds which cause the relaxation of K-80mM induced contractions in smooth muscles are considered as calcium channel antagonists [24][25][26]. The results of the present study have shown that the spasmolytic activity of thiophene derivatives may be due to the blockage of calcium channels.…”
Section: Spasmolytic Activitymentioning
confidence: 63%
“…The whole plant extract showed in vivo hypotensive and diuretic activity in normotensive rats [74]. The root extract of this species showed anti-oxidant activity (DPPH test, IC 50 = 2.006 µg/mL) [25] and asphorodin, a compound isolated from the whole plant extract, exhibit a potent inhibition of lipoxygenase enzyme, (IC 50 = 18.1 µM) [26], which may have an important role as an anti-inflammatory agent.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the literature shows that the extracts of the plant of the genus Asphodelus have been used and tested for the treatment of various pathologies, among which: Hypertension for its vasodilatory and diuretic effects, as reported by Aslam et al (2016) [19] on a study on mice reporting a vasodilator effect due to a mechanism similar to calcium channel blockers, and a diuretic effect similar to thiazides; for the treatment of gastric ulcer, Gürbüz et al (2002) shows a use of the root of Asphodelus eastivus with a gastro-protector effect [20]; Anand et al 2012 [21] and Sharma et al (2011) report a medical use, the first in Africa and the second in India, for the treatment of nephrolithiasis with an increase in diuresis [22].…”
Section: Discussionmentioning
confidence: 99%